Analysis of the incidence of the job done by the specific advisers in unique schools - Mendoza Mendoza, Luis Alfredo (2011)
The study examines the perspective of specific advice from the Spanish areas, math, social studies and science teachers and one teacher of the school circuit 05, Regional Education Directorate Santa Cruz, proper schools: Palestine, Castilla de Oro, Altos del Roble, Playa Hermosa, Cacique and New Colon, on the management carried out by consultants and educational input they expect teachers to strengthen their work in the teaching-learning process, as well as school management.With the present investigation, we identified as a problem or need, lack of training spaces and professional development of teachers one teacher for this reason, we present a management model, which considers the components related to the performance of one teacher's work . The design aims to address two major areas of school management: the administrative and teaching area.